(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the concept of patriotism and its essence, strengthening of national independence in today’s globalization processes, issues of its importance in ensuring the country’s security are scientifically and theoretically analyzed, and practical suggestions are given.